Cystic Papillary Meningioma Recurrence With Extracranial Metastasis After Surgery and Postoperative Radiotherapy. Issue 1 (February 2015) - Lou, Lin; Zhu, Junming; Zhao, Yuanyuan; Ma, Jie; Zhao, Zhongsheng; Lu, Gang
<x xml:space="preserve">Abstract</x> Meningiomas are typically benign tumors, and the papillary variant of meningioma with cyst formation is extremely rare. Here, we describe a female patient with cystic papillary meningioma in the left parietal area with cystic recurrence, brain invasion, and extracranial metastasis after gross total surgical resection and postoperative radiotherapy (RT). The solid metastatic lesion was located in the extradural mater and infiltrated into the skull. Considering the severe malignancy of this disease, gross total resection including removal of the cystic wall and adjuvant postoperative RT were deemed necessary. This is a first report of a cystic papillary meningioma with a local cystic recurrence and contemporary extracranial metastasis after gross total surgical resection and postoperative RT. Cyst formation mechanism, correlation with recurrence rates, and treatment modalities are discussed.